Inconsistency between objective and subjective comparisons of sleep quality is found between sea level and moderate terrestrial altitude (2,320m) in high-performance swimmers - Astridge, D.; McKenna, M.; Campbell, A.; Turner, A. P. (International Journal of Sports Science and Coaching, 2023)
It is popular for high-performance athletes to attend training camps at natural moderate altitude (1800-2500m), which may have direct and indirect effects on the quantity and quality of sleep athletes obtain. This can potentially influence the ability to maximise training responses and optimise recovery from exercise. This study aimed to compare objective and subjective markers of sleep quality between sea level (SL) and moderate altitude (ALT) in a sample of 14 (male n = 5, female n = 9) high-performance collegiate swimmers. Sleep was objectively (wristwatch actigraphy) and subjectively (Athlete Sleep Screening Questionnaire; ASSQ) assessed at SL and an ALT of 2,320m. A significant increase (p = 0.028, d = 0.76) in the `sleep difficulty score` calculated from the ASSQ was identified from SL (4.9 ± 1.7 au) to ALT (6.6 ± 2.3 au), with a greater number of the swimmers judged to have a more severe clinical sleep problem at ALT. Of the seven sleep characteristics assessed objectively, there were no significant differences identified between the two environments. Sleep disruption was found to substantially improve following rest/recovery days while at ALT. Although this study highlights possible inconsistencies between objective and subjective measures of sleep quality while at ALT, any suggestion of reduced sleep quality should be considered seriously. Practically, the present study demonstrates the importance of, at altitude, using both objective and subjective measures to monitor athlete sleep quality, and ensuring training schedules are carefully periodised, incorporating rest or recovery days within intense training blocks for optimal sleep quality to be achieved.